Accessibility Support in Choice of College Major and Career for High School Students During Covid 19 - Widyastuti, Liza Yudhita (Universitas Negeri Jakarta, 2024)
There are many changes in human life after arrival of Covid-19 pandemic. One of them is change in education process. Education, which was easily accessible, is more increasingly limited over the pandemic, with face-to-face activities moving online. Students also experience limitations in interacting with others to access educational information and undergo psychological changes. This exacerbates the issue where many students in Indonesia are confused about choosing their majors and future careers. When these students eventually enrol in higher education, they are at risk of choosing the wrong major and career mismatching which impacts their future career development. Therefore, the program team conduct online psychosocial education to help students recognize themselves, choose the right majors, and overcome obstacles related to major selection. There are 137 students from various regions in Indonesia participating in the online program via Zoom Meeting Cloud. Participants find the program beneficial and recommend its continuation. Overall, participants are satisfied with the implementation of the program and hope for its sustainability.